Biodiesel production from degummed Jatropha curcas oil using constant-temperature ultrasonic water bath. Issue 17 (1st September 2016) - Jogi, Ramakrishna; Murthy, Y.V.V. Satyanarayana; Satyanarayana, M.R.S.; Rao, T. Nagarjuna; Javed, Syed
ABSTRACT: This paper studied tri-basic potassium phosphate for transesterification process with degummed crude Jatropha curcas oil using constant-temperature, ultrasonic water bath generating low-intensity pulses with good energy distribution converting the maximum amount of biodiesel. Tri-basic potassium phosphate is suitable for J. curcas oil when the free fatty acid (FFA) content is less than 2%. The optimal reaction levels are catalyst 1.0 wt%, temperature of 50°C, and methanol-to-oil molar ratio of 12:1. The yield is 98% after 45 min, at 20 kHz frequency. The catalytic activity is found similar to potassium hydroxide and the catalyst solubility is only 4.27 ppm.